Aspek Perkembangan Kognitif Pada Masa Remaja - Debby Irola; Anna Dina Kalifia (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
The purpose of this research is to understand the Cognitive Development Aspects in Adolescence. The method employed is a Literature Review, gathering information from books, scientific works, etc. Cognitive Development Aspects in Adolescence are elucidated using Adolescent Cognition: (1) Piaget's Theory, (2) Adolescent Egocentrism, (3) Information Processing. The conclusion drawn is the interconnectedness of Adolescent Cognition in life development.